Removal of discretion requirements in Government decision making based on copyright law - Suhartono, Slamet; Mangesti, Yovita Arie (Research Journal in Advanced Humanities, 2025)
Elimination of conditions for the use of discretionary legislation must be followed by regulations. Article 24 point b of the Job Creation Law aims to provide more flexibility to government officials in making decisions for the purposes referred to in Article 22 paragraph (2) of the UUAP, bringing juridical implications for the use of the basis for decision making, the basis for lawsuits, and the basis for testing the validity of law (toetsingrecht) government decisions. In addition, the abolition of these conditions must also be followed by the threat of criminal sanctions for officials who commit criminal acts of corruption based on the provisions of Article 3 of the Anti-Corruption Law. This is done to avoid the escape of suspected perpetrators of corruption from the snares of the law. Because the criminal threat is based on Article 2 of the Anti-Corruption Law, if the suspect is not proven to have committed an unlawful act, then the suspect is based on the legality principle in criminal law, "no action can be punished unless it is regulated by law.